Biomedicine: A 3D Real‐Scale, Biomimetic, and Biohybrid Model of the Blood‐Brain Barrier Fabricated through Two‐Photon Lithography (Small 6/2018). Issue 6 (8th February 2018) - Marino, Attilio; Tricinci, Omar; Battaglini, Matteo; Filippeschi, Carlo; Mattoli, Virgilio; Sinibaldi, Edoardo; Ciofani, Gianni
Abstract : In article number 1702959, Attilio Marino, Omar Tricinci, Edoardo Sinibaldi, Gianni Ciofani, and co‐workers fabricate a real‐scale, biohybrid and biomimetic microfluidic model of the blood‐brain barrier through two‐photon lithography and characterize it in vitro. This image represents the concept of the approach, from the design to the cell testing, with a merging of computer‐assisted drawing, scanning electron imaging, and confocal imaging of the device.